Job Crafting and Intent to Leave: The Mediating Role of Meaningful Work and Engagement - Oprea, Bogdan; Păduraru, Lucian; Iliescu, Dragoş (Journal of career development, 2022)
Managing turnover is an essential human resource practice. One of the modern approaches that could have the potential to increase staff retention is the stimulation of employees’ job crafting, the set of changes regarding job demands and job resources that employees proactively make. Based on self-concept theory, we expected meaningful work and work engagement to serially mediate the negative relationship between job crafting and intent to leave. A cross-sectional study was conducted on a sample of 235 Romanian employees who responded to questionnaires about all variables. The mediation hypotheses were tested with bootstrapping procedures using structural equation modeling. Meaningful work and work engagement serially mediated the negative link between job crafting and intent to leave. Our results suggest that implementing job crafting interventions could reduce employees’ intentions to leave the organization. Future studies could verify whether these interventions may represent a new management practice to effectively control turnover.